Empréstimo de dispositivos de leitura em bibliotecas: Análise de experiências - Serra, Liliana Giusti [UNESP]; da Silva, José Fernando Modesto (FapUNIFESP (SciELO), 2017)
There is an increasing presence of digital books in library collections. However, their inclusion in library routines causes doubts towards their acquisition possibilities, as well as the way they can be accessed by patrons. This article alerts Brazilian libraries about the process of using digital books through lending of reading devices. Methodologically, it is a descriptive exploratory research, which collects and reviews the literature related to experiences with lending reading devices, analyzing their good and bad aspects in regards to using them to provide patrons with access to digital content. It analyzes the experiences of River Forest Public Library and Mentor Public Library (MPL) in this area. The article concludes that including reading devices is an interesting initiative for libraries, but it can not be seen as a policy to provide digital content access to patrons. However, institutions who are not familiar with digital content can offer the loan of reading devices as a first step towards using digital books.
Reading device loan in libraries: Analysis of experiences
Keywords: Digital book; Digital lending; Reading devices